2021
DOI: 10.1080/17518423.2021.1942280
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utilisation of the Infant Monitor of vocal Production (IMP) for early identification of communication impairment in young infants at-risk of cerebral palsy: a prospective cohort study

Abstract: Aim: To report prospective longitudinal data of early vocaliszations of infants identified "at-risk" of cerebral palsy (CP) for early identification of communication impairment. Method: This case-control longitudinal prospective cohort study reports on the assessment of 36 infants, 18 identified as at-risk of CP at the time of enrolment and 18 typically developing (TD) children, at three time points: 6 months, 9 months and 12 months of age, Data were obtained through criterion and norm referenced assessments o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 86 publications
3
13
0
Order By: Relevance
“…The IMP was found to be sensitive to departure from typical development in children identified as at risk of communication impairment secondary to CP [21]. Specifically, the rate of development of more complex and speech-like vocal behaviours in the infants at risk of CP was slower compared to typically developing infants, with group differences emerging at 9 months and 12 months of age, when pre-canonical and canonical babble typically emerge.…”
Section: Assessment Of Infant Vocalisations Within the Clinical Settingmentioning
confidence: 98%
See 3 more Smart Citations
“…The IMP was found to be sensitive to departure from typical development in children identified as at risk of communication impairment secondary to CP [21]. Specifically, the rate of development of more complex and speech-like vocal behaviours in the infants at risk of CP was slower compared to typically developing infants, with group differences emerging at 9 months and 12 months of age, when pre-canonical and canonical babble typically emerge.…”
Section: Assessment Of Infant Vocalisations Within the Clinical Settingmentioning
confidence: 98%
“…Nathani and Oller [9] suggest the pre-canonical stages may "yield predictive power comparable to that which has been found with the onset of canonical babble" (p. 322), which has relevance to early identification of communication impairment in the CP population. To this end, Ward et al [21] reported on the assessment of infant vocalisations using the Infant Monitor of vocal Production (IMP, [28,35,36]) as a potentially predictive tool for use within the clinical environment.…”
Section: Assessment Of Infant Vocalisations Within the Clinical Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Sensory processing problems are experienced in children with CVI [ 14 ]; however, to our knowledge, there is no sensory integration intervention study in children with CVI. When studies with infants and children with CP were examined, it was observed that the literature has mainly included physical, cognitive, and language-speech assessment studies and intervention studies [ 15 , 16 , 17 ]. There are also sensory integration assessment and intervention studies [ 6 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%